Impact of Payments for Ecosystem Services on Deforestation in Mexico: Preliminary Lessons for REDD - Sims, Katharine; Shapiro, Elizabeth; Alix-Garcia, Jennifer (Land Tenure Center, University of Wisconsin, 2010)
The brief summarizes an evaluation of the environmental effectiveness of Mexico's national Payments for Hydrological Services program, which compensates rural landowners for avoided deforestation. The evaluation found that in an early year of implementation Mexico?s program had a small to moderate but significant effect in reducing deforestation, indicating that financial compensation policies can be effective in preventing environmental degradation. The research also suggests that some slippage of deforestation may have occurred, implying that avoided deforestation is best accounted for at a regional or national level.
Keywords: avoided deforestation; deforestation slippage; REDD policy; payments for ecosystem services; Mexico's payments for hydrological services; deforestation